Multi-Omics for the Understanding of Brain Diseases - Chiara Villa (MDPI AG, 2021)
Brain diseases, including both neurodegenerative diseases and mental disorders, represent the third largest healthcare problem in developed countries, after cardiovascular disorders and cancer [...]